Zlučovanie a rozdelenie slovenských obcí - Tekeli, Jozef (Wydział Prawa i Administracji Uniwersytetu Rzeszowskiego, 2013)
In the conditions of the Slovak Republic, an enactor rates merging and dividing of municipalities as one of the most fundamental possible changes of the municipality area, while their realization is conditioned by strict mechanisms. Merging or dividing of municipalities can be realized only on the basis of a governmental regulation issued on the consent of a concrete municipality and after the district office in the seat of the county, to which the area of the municipality belongs, uttered its attitude. When the municipality agrees, it communicates the opinion of its inhabitans presented in a positive result of a realized municipality referendum. Juridical mode of merging and dividing of Slovak municipalities is determined by the character of Slovak municipality self-government, for which a considerable fragmentation of the municipality self-government is typical. According to the valid legal status both juridical institutions are built on the principle of volunteering, but it has to be stated that in the last years justified requirements for the necessity of involuntary administrative merging of the Slovak municipalities are very often raised while searching for a solution of the problem of the fragmentation of the local self-government. In my opinion the most suitable solution is creating more categories of separate individual municipalities with different levels of adminstrative competence.

W warunkach Republiki Słowackiej łączenie i podział gmin ustawodawca traktuje jako jedną z najbardziej podstawowych z możliwych zmian w obszarach gmin, podczas gdy ich realizacja jest uwarunkowana przez restrykcyjne mechanizmy. Łączenie lub podział gminy może być zrealizowany jedyne w oparciu o rozporządzenie rządu wydane po uzyskaniu zgody danej gminy oraz uprzedniego zasięgnięcia opinii urzędu okręgu, do którego gmina należy. Gdy gmina wyrazi zgodę, wówczas przekazuje opinię swoich mieszkańców, wyrażoną w formie pozytywnego wyniku gminnego referendum. Tryb prawny łączenia i dzielenia słowackich gmin uzależniony jest od rodzaju gminy w systemie samorządu gminnego, dla którego charakterystyczna jest znaczna fragmentaryzacja. Zgodnie z obowiązującym stanem normatywnym, obie instytucje prawne są zbudowane na zasadzie dobrowolności, ale należy stwierdzić, że w ubiegłych latach pojawiała się uzasadniona potrzeba przymusowego administracyjnego łączenia słowackich gmin, którą często artykułowano podczas poszukiwania rozwiązań problemu nadmiernej fragmentaryzacji samorządu lokalnego. W moim przekonaniu najbardziej odpowiednim rozwiązaniem jest tworzenie większej liczby kategorii odrębnych gmin o różnym zakresie uprawnień administracyjnych.
Merging and Splitting Municipalities in the Slovak Republic
Keywords: territory of the municipality; obszar gminy; zmiana obszaru; łączenie gmin; podział gmin; referendum lokalne; określone warunki; territory changes; municipalities‘ merging; municipalities‘ splitting; local referendum; strict conditions